The Impact of Taxpayer Awareness, Tax Service Quality, Tax Counseling, and Tax Sanctions on Individual Taxpayer Compliance - Manurung, Agus Sagita; Ardillah, Kenny (Universitas Padjadjaran, 2024)
This study aims to examine the effect of taxpayer awareness, tax service quality, taxpayer counseling, and tax sanctions on individual taxpayer compliance at the Pulo Gadung Pratama Tax Service Office. The independent variables in this study are taxpayer awareness, tax service quality, taxpayer counseling, and tax sanctions, while the dependent variable is individual taxpayer compliance. The research population is in Pulogadung with a total sample of 100 individual taxpayers. This study uses primary data and simple random sampling method. The results of this study show that taxpayer awareness, tax service quality, tax counseling, and tax sanctions have a positive effect on individual taxpayer compliance.